Individuální titanová acetabulární komponenta vyrobená 3D tiskem: výhody a limity použití - Macák, D; Džupa, V; Krbec, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2021)
The authors report on three cases in which a custom-made 3D printed titanium acetabular component of total hip arthroplasty was used to manage an advanced acetabular bone defect with pelvic discontinuity. The implant surface structure impeded long-term bone integration. Nonetheless, the stable bridging of the acetabular defect resulted in full integration of impacted bone allografts at the base of the implant. The pelvic continuity was restored within 12 months after surgery, and thus the acetabulum was prepared for potential further implantation of a standard revision acetabular component. Only one of the three female patients underwent a revision surgery at 18 months after surgery, the other two female patients were satisfied to such a degree with the clinical outcome at 6 years and 5 years, respectively, after surgery that they refused to undertake the revision surgery, despite X-ray images showing signs of loosening of the custom-made titanium acetabular component. The authors concluded that the implantation technique of three-point fixed custom-made 3D printed acetabular component made of titanium combined with impaction grafting of the acetabular base is a good alternative in managing the advanced bone defects of acetabulum with pelvic discontinuity after the failure of total hip arthroplasty. Even though inadequate surface porosity of the thus produced component did not allow its permanent osteointegration, the assembly was stable enough to allow the bone allografts to rebuild and restore continuity of the pelvis and facilitated future implantation of the standard revision acetabular component. Key words: 3D printing, individual acetabular component, titanium, total hip prosthesis, revision hip arthroplasty, acetabular reconstruction, custom-made implants.
Keywords: výsledek terapie; Acetabulum; Prosthesis Failure; Prosthesis Design; kyčelní protézy; acetabulum; protézy - design; následné studie; titan; Titanium; náhrada kyčelního kloubu; Follow-Up Studies; Treatment Outcome; Hip Prosthesis; lidé; Arthroplasty, Replacement, Hip; ženské pohlaví; Humans; 3D tisk; Printing, Three-Dimensional; Reoperation; selhání protézy; Female; reoperace